Network Pharmacology and Experimental Verification Strategies to Illustrate the Mechanism of Jian-Pi-Yi-Shen Formula in Suppressing Epithelial–Mesenchymal Transition - Zhao, Yuan; Li, Xiangbin; Wang, Fochang; Huang, Shiying; Du, Hanqian; Li, Shunmin; Chen, Jianping (Frontiers in Pharmacology, 2022)
Jian-Pi-Yi-Shen formula (JPYSF), a traditional Chinese medicine, has been recommended to treat renal fibrosis for decades. Previous studies had shown that JPYSF could inhibit epithelial-mesenchymal transition (EMT), an important regulatory role in renal fibrosis. However, the mechanism of JPYSF action is largely unknown. In this study, network pharmacology and experimental verification were combined to elucidate and identify the potential mechanism of JPYSF against renal fibrosis by suppressing EMT in molecular and pathway levels. Network pharmacology was first performed to explore the mechanism of JPYSF against renal fibrosis targeting EMT, and then 5/6 nephrectomy (5/6 Nx)-induced rat model of renal fibrosis was conducted to verify the predictive results by Masson’s trichrome stains and western blot analysis. 232 compounds in JPYSF were selected for the network approach analysis, which identified 137 candidate targets of JPYSF and 4796 known therapeutic targets of EMT. The results of Gene Ontology (GO) function enrichment analysis included 2098, 88 and 133 GO terms for biological processes (BPs), molecular functions (MFs) and cell component entries, respectively. The top 10 enrichment items of BP annotations included response to steroid hormone, metal ion, oxygen levels, and so on. Cellular composition (CC) mainly enriched in membrane raft, membrane microdomain, membrane region, etc. MF of JPYSF analysis on EMT was predominately involved in proximal promoter sequence-specific DNA binding, protein heterodimerization activity, RNA polymerase II proximal promoter sequence-specific DNA binding and so on. The involvement signaling pathway of JPYSF in the treatment of renal fibrosis targeting EMT were associated with anti-fibrosis, anti-inflammation, podocyte protection and metabolism regulation. Furthermore, the in vivo experiments confirmed that JPYSF effectively ameliorated interstitial fibrosis and inhibited the overexpression of α-SMA, Wnt3a and β-catenin, and increased the expression of E-cadherin by wnt3a/β-catenin signaling pathway in 5/6 Nx-induced renal fibrosis rats. Using integrative network pharmacology-based approach and experimental verification, the study showed JPYSF had therapeutic effects on EMT by regulating multi-pathway, among which Wnt3a/β-catenin signaling pathway was one proven pathway. These findings provide insights into the renoprotective effects of JPYSF against EMT, which could suggest directions for further research of JPYSF in attenuating renal fibrosis by suppressing EMT.